Markets as Cultures: An Ethnographic Approach - Митчел Аболафия (Journal of Economic Sociology, 2010)
The approach to the markets as cultures supposes at least three fields of studies: constitutive rules and roles; local rationality; dynamics of authorities and changes. The paper deals with each of the fields. The methodological issues of the study the markets as cultures are discussed after that. The author supports his statement by giving examples of his own ethnographic studies of the stock exchange, bond market and futures markets on the Wall-street.